Genetic Differentiation in Red and Green Noctiluca scintillans in Jakarta Bay, Indonesia - Muhammad Izzat Nugraha; Goh Nishitani; Akira Ishikawa; Sutanto Hadi; Waka Sato-Okoshi; Beginer Subhan (Journal of Marine Science and Engineering)
Marine dinoflagellate Noctiluca scintillans occurs in two forms, red and green, that overlap in distribution across the Arabian Sea and Southeast Asian coastal waters, particularly in Indonesia. However, limited genetic data on Indonesian N. scintillans cast uncertainty on their taxonomic status. In this study, we introduce the first 28S PCR primer set specifically designed for Noctiluca to enable sequence analysis. The Indonesian red-type N. scintillans (RNS) sequences show considerable divergence from other documented populations, suggesting a potentially adapted population in Jakarta Bay. Similarly, the RNS in Indonesia differ genetically from co-occurring green-type N. scintillans (GNS). Morphological differences were also observed between Indonesian and Japanese RNS, with Indonesian cells exhibiting a smaller size and rougher surface, in contrast to the larger size and smoother surface observed in Japanese specimens.